Analysis of special area plan on facade of shophouses in Taiping heritage town / Anne Foo Mei Mei - Anne Foo, Mei Mei (2018)
Heritage towns in many countries are facing the pressure of rapid growth and redevelopment due to economic needs and also in the name of tourism. However, it is unfortunate that many a times, the conservation process is separated from the development planning cum redevelopment process rendering a town placeless and loses its sense of belonging. The realization on the value and importance of conserving the cultural heritage always only comes into the picture when this heritage has been lost or damaged and irreplaceable. Realizing this, the international community has put in significant effort to address this issue and has proved that it is possible to protect our heritage and have redevelopment hand in hand as these projects have proven to be a success if not better. Thus, Malaysia has identified and selected thirty-four towns under the Special Area Plan (SAP) development whereby Taiping was also enlisted with its declaration as a Heritage Town in 1999. There were also intentions to have Taiping listed under the UNESCO Heritage list similar to Malacca and Georgetown; and if this is to be realized, development in Taiping has to be carried out with much care and caution. The Taiping Special Area Plan (TSAP 2010) was launched in 2010 with seven development plans set within Taiping Town Conservation Zone (TTCZ) and the Taiping Lake Gardens Conservation Zone. This study seeks to explore the level of change and type of change to the façade characteristics of buildings within TTCZ since the implementation of TSAP 2010. The research adopted a case study strategy as the research method. A field study was carried out on TTCZ to first create an inventory comprising photo evidence of all the 1132 units located within the designated zone. A cross analysis was carried out with the photographic data from the inventory with archival data. A document review of the TSAP 2010 guidelines were also carried out so as to explore the adherence of these buildings with changes to the guidelines. The first findings have revealed that there were changes to the building’s façade characteristics though on the overall the magnitude of change was low. Secondly, building units were found to have changed in its form, proportion, rhythm, materials and colours. Thirdly, majority of building units with changes did not adhere to the TSAP 2010 guidelines. From the findings, the low level of change is likely because these building units have already changed prior to 2010. Building units that have shown changes may be due to a change in ownership, a change in use of the unit, the questionable structural condition of the building and the economic viability in redevelopment. There may be also issues of implementation with the low level of conformance to the guidelines. However, these assumptions need to be studied further for verification. Hence, Taiping’s initial aim of being listed as a UNESCO heritage town may be affected with the changes but it is with hope that the old glory of Taiping could be maintained, retained and preserved further.